The changing role of the embryo in evolutionary thought : roots of evo-devo - Amundson, Ronald (Cambridge studies in philosophy and biology., 2005)
"In this book Ron Amundson examines 200 years of scientific views on the evolution-development relationship from the perspective of evolutionary developmental biology (evo-devo). This new perspective challenges several popular views about the history of evolutionary thought by claiming that many earlier authors made history come out right for the Evolutionary Synthesis." "This book will appeal to students and professionals in the philosophy of science, and the philosophy and history of biology."--Jacket